Evaluation of planting densities of tomato (Lycopersicon esculentum Mill) in greenhouse. - Cruz-Carrillo, José (2003)
Thisresearch was conduted out in the Technological Institute ofAgriculture of Oaxaca. N. 23 located at the Ex Hacienda deNazareno, Xoxocotlan, Oaxaca, in order to evaluate theeffect of three planting densities on the vegetativedevelopment and production of different tomato hybridswith growth habit, cultivated in greenhouse. The tomatohybrids were SXT, DRW3410 and SXT0289. The resultsshow that it wasn.t a statistic difference for the hybrids,only for the planting densities, of 5.3 plants/m2 and 4plants/m2 with 17.52 y 17.37 kg/m2, respectively; wichrepresents a yield average of 151.6 t/ha.